Predictors of Continuation and Cessation of Nonsuicidal Self-Injury - Andrews, Tori; Martin, Graham; Hasking, Penelope; Page, Andrew (Elsevier, 2013)
Purpose: This paper reports the first prospective study of risk factors for continuation of non-suicidal self-injury (NSSI) during adolescence. Methods: We examined whether NSSI became more severe among those continuing to self-injure 1 year later, as well as characteristics and predictors of continuation, relative to cessation, drawn from a sample of 1,973 community-based adolescents from five states in Australia. Multiple sociodemographic and psychosocial factors were assessed in a series of sequential logistic regressions. Results: Of those reporting NSSI at follow-up (12% total sample), 4.1% (95% CI: 3.3%–5.0%; n = 80) continued from baseline and an additional 4.1% had stopped this behavior by follow-up (95% CI: 3.3%–5.1%, n = 81; 3.8% new cases). Frequency, potential lethality and number of methods of NSSI increased among adolescents continuing to self-injure. These individuals also had overall higher frequency and more serious wounds compared with those who had stopped self-injuring, possibly providing parameters to differentiate these groups. Continuation of NSSI was associated with higher frequency (OR = 1.06; 95% CI = .99–1.13, p = .08), lower cognitive reappraisal (OR = .86; 95% CI = .78–.95, p = .004) and higher emotional suppression (OR = 1.10; 95% CI = .98–1.22, p = .09) relative to cessation at T1. Conclusions: These findings may assist to better identify young people more likely to continue self-injuring and also highlight potentially modifiable factors to inform early intervention initiatives.